Determination of optimal load in the Wingate Anaerobic Test is not depend on number of sprints included in mathematical models - Michalik, Kamil; Smolarek, Marcin; Ochmann, Bartosz; Zatoń, Marek (Frontiers in Physiology, 2023)
Determining the optimal load (OPTLOAD) of generating peak power output (PPO) is important in diagnosing anaerobic potential. The study aimed to compare the calculated, optimal load based on the force-velocity test (FVT) depending on the number of sprints included in the model and to compare the PPO determined in this way with that measured in the classic Wingate anaerobic test (WAnT). The study involved 15 men, academic athletes, aged 22.4±2.3 (years), height 178.9±6.8 (cm), and body weight 77.9±12.2 (kg). During the first visit to the laboratory, they performed a 30-s lower limb WAnT (with a load of 7.5% of body weight). Visits 2-4 included a force-velocity test, i.e. nine maximum sprints with a randomly selected load from 3 to 11 kg (three 10-s sprints in a session). Three, four, five, and nine sprints in the power-velocity (P-v) and power-% body mass (P-%BM) models were included in the calculations. OPTLOAD did not differ statistically significantly depending on the number of sprints (F3,56=0.174, p=0.91, η2=0.01) and was 13.8±3.2 (%BM) for three sprints, 14.1±3.5 (%BM) for four sprints, 13.5± 2.8 (%BM) for five sprints and 13.4±2.6 (%BM) for nine sprints. The determined PPO did not differ regarding the number of sprints between the models based on the P-v and P-%BM dependencies. Moreover, the PPO measured during WAnT (870.6±179.1 W) was statistically significantly lower by 232.3–263.6 (W) in the P-v model (F4,70=3.044, p=0.02, η2=0.148), and for P-%BM (F4 .70=2.976, p=0.02, η2=0.145) the difference was 236.3–268.1 (W). The use of an individual approach in the form of three sprints in FVT allows us to determine OPTLOAD and extrapolate PPO. The results suggest that the load used in the Wingate Anaerobic test of 7.5% of body weight is significantly undervalued, which affects the underestimated value of the maximum power of academic athletes.